Dhalion: Self-Regulating Stream Processing in Heron - Floratou, Avrilia; Agrawal, Ashvin; Graham, Bill; Rao, Sriram; Ramasamy, Karthik (Proceedings of the VLDB Endowment, 2017)
In recent years, there has been an explosion of large-scale real-time analytics needs and a plethora of streaming systems have been developed to support such applications. These systems are able to continue stream processing even when faced with hardware and software failures. However, these systems do not address some crucial challenges facing their operators: the manual, time-consuming and error-prone tasks of tuning various configuration knobs to achieve service level objectives (SLO) as well as the maintenance of SLOs in the face of sudden, unpredictable load variation and hardware or software performance degradation. In this paper, we introduce the notion of self-regulating streaming systems and the key properties that they must satisfy. We then present the design and evaluation of Dhalion, a system that provides self-regulation capabilities to underlying streaming systems. We describe our implementation of the Dhalion framework on top of Twitter Heron, as well as a number of policies that automatically reconfigure Heron topologies to meet throughput SLOs, scaling resource consumption up and down as needed. We experimentally evaluate our Dhalion policies in a cloud environment and demonstrate their effectiveness. We are in the process of open-sourcing our Dhalion policies as part of the Heron project.